Spanish galleon off coast of California - McAllister, Parker S. (1903-1970) (1954)
Dramatized representation of a 1602 Spanish exploration expedition of the California coast commanded by Sebastián Vizcaíno. A full-sailed galleon flying Spanish colors and bearing a large cross on one sail rides the waves. Parker McAllister, born in 1903 in Massachusetts, was a Seattle Times artist from 1924 to 1965. McAllister started his career as an illustrator at 14 for a Spokane publication; he joined the art staff at the Seattle Times in 1920. His first Sunday magazine cover was a poster-type illustration celebrating the University of Washington crew races in spring 1924. During McAllister's career, he created illustrations depicting “local color” events and situations now routinely handled by photographers. As the technology improved, he expanded his repertoire - he illustrated articles, drew covers for special sections and the weekly Seattle Sunday Times Magazine, and drew diagrams, comics, cartoons, and portraits for the Times’ editorial page. In 1956, an exhibition of his watercolor and oil paintings of Pacific Northwest scenes and historical incidents - including some paintings from the “Discovery of the Pacific Northwest” series - were exhibited at the Washington State Historical Society Museum in Tacoma. He was also a member of the Puget Sound Group of Men Painters. McAllister retired from the Seattle Times in 1965; he passed away in Arizona in 1970. Watercolors Painting appeared on the cover of the Seattle Times Magazine on December 12, 1954 as part of the feature series “Discovery of the Pacific Northwest” written by Lucile McDonald and also later appeared in the book based on the series, Search for the Northwest Passage by Lucile McDonald. McAllister and McDonald also collaborated in a similar way to produce Washington’s Yesterdays.